FEO-RICH, PORPHYRITIC PYROXENE CHONDRULES IN UNEQUILIBRATED ORDINARY CHONDRITES - Jones R.H. (My University, 1996)
A suite of FeO-rich (type II), porphyritic, olivine/pyroxene (POP) chondrules has been studied in detail. Data for ten chondrules from Semarkona (LL3.0) are emphasized, and one chondrule from Chainpur (LL3.4) and two from Parnallee (LL3.6) are included as further examples of certain properties. The chondrules contain phenocrysts of pyroxene and olivine in varying proportions, and have Fe/(Fe + Mg) > 10 mol% in all the silicate minerals. Four pyroxene minerals are present: clinoenstatite, orthorhombic enstatite, pigeonite, and augite. Pyroxene phenocrysts may consist of all four minerals, with progressive overgrowths in order of increasing Wo content. Enstatite may occur independently of clinoenstatite, but Ca-rich pyroxenes (pigeonite and augite) always nucleate on low-Ca pyroxene phenocrysts. Pyroxene and olivine phenocrysts may be independent of each other, or may be intergrown, and commonly show hopper morphologies indicative of rapid growth. Pyroxenes and olivines are commonly strongly zoned as a result of fractional crystallization of the chondrules. In addition, low-Ca pyroxene may contain ghost regions of slightly more FeO- and minor element-rich material in the cores of grains. These regions are partially resorbed and appear to be derived from previous crystallization of essentially the same chondrule. Oscillatory zoning is observed in enstatite in two chondrules, and is believed to be the result of disequilibrium kinetic effects. Relict grains, including a forsterite relict and a partially reduced FeO-rich relict in the same chondrule, and clinoenstatite cores of pyroxene phenocrysts in another chondrule, are evidence for recycling and mixing of chondrule material. All of the chondrules are highly disequilibrium assemblages. They appear to have cooled from essentially molten droplets, with little volatile loss or recondensation occurring during the heating event. Peak temperatures were probably close to liquidus temperatures, 1500-1700oC, and cooling rates were probably of the order of hundreds of degrees per hour. This description will serve as a basis for future interpretation of the effects of metamorphism on porphyritic, pyroxene-rich chondrules.